AKULTURASI BUDAYA JAWA DAN SUNDA TERHADAP PENERAPAN SISTEM PENGENDALIAN MANAJEMEN PADA PT. X - Azalea Anasthasia B.; Sujoko Efferin (CALYPTRA, 2018)
Abstract- This study analyzes the acculturation of Javanese and Sundanese culture because there is rarely any research on the acculturation of these two cultures and their influence on the application of Management Control System. The company that became the object of research is in Cibadak which majority of the workers are Sundanese. However, the production manager who organizes these workers is Javanese. This research is included in explanatory research which aims to give an analysis of how the acculturation of Javanese culture and Sundanese culture towards the application of MSS in the production process of PT. X. The Influence of Java and Sundanese Culture in Application of SPM on Production Process of PT. X such as the process of recruiting labor based on subjective assessment of production manager, no formal training for the workers, establishing close relationships with the workers, giving vision and mission orally, giving individual rewards through absenteeism, no routine employee shifting, production manager Participate in the operational activities of production, and the value of gotong royong in production activities.